A Note on non-relativistic gravitation - Hillion, Pierre (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Using the Jefimenko theory of gravitation [1] and the Le-Bellac, Levy-Leblond non relati-vistic approximations of Maxwell equations, we prove that in addition to newtonian gravi-tation, there exists a second non-relativistic gravitation.